Japan as a global military power : new capabilities, alliance integration, bilateralism-plus - Hughes, Christopher W. (Cambridge, United Kingdom ; New York : Cambridge University Press, 2022)
"Japan is emerging as a more prominent global and regional military power, defying traditional categorisations of a minimalist contribution to the US-Japan alliance, maintaining anti-militarism, seeking an internationalist role, or carving out more strategic autonomy. Instead, this Element argues that Japan has fundamentally shifted its military posture over the last three decades and traversed into a new categorisation of a more capable military power and integrated US ally. This results from Japan's recognition of its fundamentally changing strategic environment that requires a new grand strategy and military doctrines. The shift is traced across the national security strategy components of Japan Self-Defence Forces' capabilities, US-Japan alliance integration, and international security cooperation. The Element argues that all these components are subordinated inevitably to the objectives of homeland security and re-strengthening the US-Japan alliance, and thus Japan's development as international security partner outside the ambit of the bilateral alliance remains stunted. This title is also available as Open Access on Cambridge Core"--
Introduction: Japan's new military profile -- Japan's shifting strategic and military outlook -- Transforming defence doctrine and capabilities -- US-Japan alliance integration -- International cooperation : still bilateralism-plus -- Conclusion : regional and global implications.
First published 2022
Includes bibliographical references
AAL
Donated by Embassy of Japan in Bangladesh, Read Japan Project 2025, The Tokyo Foundation, supported by The Nippon Foundation.
Keywords: National security -- Japan; Security, International; Japan -- Military policy; Japan -- Strategic aspects